2010
DOI: 10.1021/jp105971s
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hydration and Cationic Sites of Nanohydroxyapatites with Amorphous or Crystalline Surfaces: A Comparative Study

Abstract: This paper is an extension of previous work devoted to the characterization of platelet-like hydroxyapatite (HA) nanoparticles constituted by a crystalline core coated by an amorphous surface layer 1-2 nm thick (Bertinetti et al. J. Phys. Chem. C. 2007, 111, 4027-4035). By increasing the preparation temperature, the platelet morphology was retained but HA nanoparticles exhibited a higher degree of crystallinity (evaluated by X-ray diffractometry). High-resolution transmission electron microscopy revealed that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 38 publications
(77 reference statements)
6
99
0
1
Order By: Relevance
“…A more precise problem [47] stands in line with this way of thinking: "Focusing on nano-HAp morphology, needlelike [48][49][50][51] and platelike [52][53][54] nano-particles can be prepared, while in bone tissue only the second type seems to be present [55][56][57]. For both morphologies the prevailing surface terminations are of the {010} type, which in the case of needlelike nano-HAp are the lateral facets of the hexagonal nano-particles elongated along the crystallographic c-axis, while, for the platelike nano-particles they are the basal facets of nano-particles preferentially grown along both the c-and a-(or b-) axis [53,54,58] breaking the crystal symmetry through a mechanism still matter of investigation [52,58].…”
Section: Solved and Unsolved Problems About The Relationship Between mentioning
confidence: 97%
“…A more precise problem [47] stands in line with this way of thinking: "Focusing on nano-HAp morphology, needlelike [48][49][50][51] and platelike [52][53][54] nano-particles can be prepared, while in bone tissue only the second type seems to be present [55][56][57]. For both morphologies the prevailing surface terminations are of the {010} type, which in the case of needlelike nano-HAp are the lateral facets of the hexagonal nano-particles elongated along the crystallographic c-axis, while, for the platelike nano-particles they are the basal facets of nano-particles preferentially grown along both the c-and a-(or b-) axis [53,54,58] breaking the crystal symmetry through a mechanism still matter of investigation [52,58].…”
Section: Solved and Unsolved Problems About The Relationship Between mentioning
confidence: 97%
“…Still, in recent years, several studies [102][103][104][105] revealed that HA nanoparticles can be coated by an amorphous, non-apatitic surface layer surrounding a crystalline hydroxyapatite bulk. However, the possibility of obtaining apatitic particles with crystalline structure extended up to the surface was recently reported [106]. In addition, HA surface feature may be modified by exchanging part of calcium ions with other divalent cations.…”
Section: The Inorganic Bone Matrix: Hydroxyapatitementioning
confidence: 99%
“…The highest shift is attributed to a tiny fraction of the most exposed calcium ions, which are those modeled in our studies, so proving a good agreement. On the other hand, the majority of calcium sites contribute to the lowest shift (Bertinetti et al, 2007;Sakhno et al, 2010).…”
Section: Adsorption Of H 2 O and Co Upon The Most Exposed Ca Ions Of mentioning
confidence: 99%